2020
DOI: 10.1371/journal.pone.0232965
|View full text |Cite
|
Sign up to set email alerts
|

The double-edged sword role of fibroblasts in the interaction with cancer cells; an agent-based modeling approach

Abstract: Fibroblasts as key components of tumor microenvironment show different features in the interaction with cancer cells. Although, Normal fibroblasts demonstrate anti-tumor effects, cancer associated fibroblasts are principal participant in tumor growth and invasion. The ambiguity of fibroblasts function can be regarded as two heads of its behavioral spectrum and can be subjected for mathematical modeling to identify their switching behavior. In this research, an agent-based model of mutual interactions between f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Our simulations demonstrated that fibroblasts can cause a faster failure of adaptive therapy. In tumors, fibroblasts influence the growth of the tumor cells in a spectrum of ways [48][49][50][51]. For example, in breast cancer, fibroblasts increase the growth by secreting epidermal growth factor (EGF); furthermore, the transforming growth factor-β (TGF-β) produced by the tumor cells converts fibroblasts into myofibriblasts, which increase the secretion of EGF and thus cause even more rapid tumor progression [52].…”
Section: Discussionmentioning
confidence: 99%
“…Our simulations demonstrated that fibroblasts can cause a faster failure of adaptive therapy. In tumors, fibroblasts influence the growth of the tumor cells in a spectrum of ways [48][49][50][51]. For example, in breast cancer, fibroblasts increase the growth by secreting epidermal growth factor (EGF); furthermore, the transforming growth factor-β (TGF-β) produced by the tumor cells converts fibroblasts into myofibriblasts, which increase the secretion of EGF and thus cause even more rapid tumor progression [52].…”
Section: Discussionmentioning
confidence: 99%
“…Our simulations demonstrated that fibroblasts can cause a faster failure of adaptive therapy. In tumors, fibroblasts influence the growth of the tumor cells in a spectrum of ways [58][59][60][61]. For example, in breast cancer, fibroblasts increase the growth by secreting epidermal growth factor (EGF); furthermore, the transforming growth factor-β (TGF-β) produced by the tumor cells converts fibroblasts into myofibroblasts, which increase the secretion of EGF and thus cause even more rapid tumor progression [62].…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Interactions mediating metabolic changes and phenotypic adaptations [ 207 ], evolution of several metabolites and their inhibition [ 208 ], tumor specific alterations [ 209 ], and models of the Warburg effect such as genome-scale computational study of metabolic targets inhibiting cancer migration [ 210 ] or models behind the glycolytic switch [ 211 ]. A very recent study [ 212 ] proposes an agent-based dynamic model to investigate the role of CAFs further; however, it focuses almost exclusively on their crosstalk with cancer cells and does not consider metabolic reprogramming.…”
Section: Computational Systems Biology Approachesmentioning
confidence: 99%